The Roles of Quantity Surveyor in Sustainable Development within the Context of Maqasid Shariah and the Concept of Khalifa - Ahmad Nizam, Ahmad Aliff; Hasan, Sharina Farihah (Research in Management of Technology and Business, 2024)
Maqasid Shariah and the concept of khalifa can direct sustainable practices because it is a holistic way of life. Maqasid Shariah provides a comprehensive framework for Islamic values and objectives while the concept of khalifa sees human as the representative in managing the earth. Sustainable development is the development that meets present needs without compromising future generations therefore, in line with the concept of Maqasid Shariah and khalifa. Professionals play a vital role in sustainable development, and among them, quantity surveyors are especially important. Existing literature on the roles of quantity surveyors in sustainable development primarily focuses on environmental and economic aspects, limited attention may be given to the integration of Islamic concepts. Understanding the role of quantity surveyors in sustainable development within the context of Maqasid Shariah and khalifa is paramount. This paper seeks to answer the question of whether the roles and responsibilities of quantity surveyors in sustainable development are in line with the concept of Maqasid Shariah and khalifa. Methodology for the study involves reviews of relevant literature and structured interviews with experts. The findings indicate that quantity surveyors have the opportunity to implement the concept of Maqasid Shariah and khalifa into their roles in sustainable development.